(untitled) (Eventum: A Journal of Medieval Arts & Rituals, 2023)
The surviving Viennese town-books of around 1400 contain more than 2000 entries that are last wills which often mention the bequest of postmortem proxy pilgrimages to be undertaken for the deceased. This article analyses postmortem Viennese proxy pilgrimages in a quantitative and qualitative way regarding chronological, financial, and gendered aspects and patterns. It also compares these pilgrimages with those of another neighboring city, Pressburg (today Bratislava) which took place from the twenties of the fifteenth century onwards. As shown, the rich collections of last wills involving Pressburg exhibit both similarities with and differences from the Viennese proxy pilgrimages.